INFLUENCE OF SOAKING DURATION AND PARTICLE SIZE ON ANTIOXIDANT ACTIVITY AND PHYTOCHEMICAL CHARACTERISTICS OF Uncaria Gambir Roxb ETHANOLIC LEAF EXTRACT TEA: PENGARUH DURASI PERENDAMAN DAN UKURAN PARTIKEL TERHADAP AKTIVITAS ANTIOKSIDAN DAN KARAKTERISTIK FITOKIMIA TEH EKSTRAK DAUN Uncaria Gambir Roxb DALAM ETANOL - Dodi Iskandar; D.U.M Susilo; Erning Indrastuti; Rendy Fikrian Akmal (ROCE : Jurnal Pertanian Terapan, 2026)
Environmental pollution and modern lifestyles increase human exposure to free radicals, which contribute to various degenerative diseases. Antioxidants play a crucial role in neutralizing free radicals and preventing oxidative damage. Uncaria gambir Roxb., a tropical plant widely used in Indonesia, is rich in polyphenolic compounds, particularly catechins, with strong antioxidant potential. This study aimed to evaluate the antioxidant activity of ethanolic extracts of Uncaria gambir leaves through an integrated approach involving in silico prediction, extraction optimization, phytochemical screening, and in vitro antioxidant testing. Bioactive compounds were first screened using PASS Online to predict antioxidant and free radical scavenging activities. Ethanolic maceration was conducted using different particle sizes and maceration times, followed by yield determination. Phytochemical screening was performed to identify major secondary metabolites, and antioxidant activity was assessed using the DPPH radical-scavenging assay. In silico analysis indicated that most polyphenolic compounds exhibited high antioxidant potential. The highest extraction yield was obtained using a 60-mesh particle size and a 6-hour maceration period. Phytochemical screening confirmed a strong presence of phenolic compounds, and the DPPH assay showed a dose-dependent antioxidant response with a low IC₅₀ value, indicating strong antioxidant activity. These findings demonstrate that optimized ethanolic extracts of Uncaria gambir leaves have significant potential as natural antioxidant sources.